An overview of Dent disease - Eun Mi Yang; Seong Hwan Chang (Korean Society of Pediatric Nephrology, 2023)
Dent disease is a rare inherited kidney tubulopathy caused by mutations in either the CLCN5 (Dent disease 1) or OCRL1 (Dent disease 2) genes, and which is often underdiagnosed in practice. A diagnosis is clinically suspected in patients with low-molecular-weight proteinuria, hypercalciuria, and one of the following: hematuria, nephrolithiasis, nephrocalcinosis, hypophosphatemia, or chronic kidney disease. Inheritance is X-linked recessive, meaning, these symptoms are generally only found in males; female carriers may have mild phenotypes. Genetic testing is only a method to confirm the diagnosis, approximately 25% to 35% of patients have neither the CLCN5 nor OCRL1 pathogenic variants (Dent disease 3), making diagnosis more challenging. The genotype-phenotype correlations are not evident with the limited clinical data available. As with many other genetic diseases, the management of patients with Dent disease concentrates on symptom relief rather than any causative process. The current treatments are mainly supportive to reduce hypercalciuria and prevent nephrolithiasis. Chronic kidney disease progresses to end-stage between the ages of the third to fifth decades in 30% to 80% of affected males. In this review, we aimed to summarize the literature on Dent disease and reveal the clinical characteristics and molecular basis of Korean patients with Dent disease.